Kinetic control on Zn isotope signatures recorded in marine diatoms. (1st August 2017) - Köbberich, Michael; Vance, Derek
Abstract: Marine diatoms dominate the oceanic cycle of the essential micronutrient zinc (Zn). The stable isotopes of zinc and other metals are increasingly used to understand trace metal micronutrient cycling in the oceans. One clear feature of the early isotope data is the heavy Zn isotope signature of the average oceanic dissolved pool relative to the inputs, potentially driven by uptake of light isotopes into phytoplankton cells and export to sediments. However, despite the fact that diatoms strip Zn from surface waters across the Antarctic polar front in the Southern Ocean, the local upper ocean is not isotopically heavy. Here we use culturing experiments to quantify the extent of Zn isotope fractionation by diatoms and to elucidate the mechanisms driving it. We have cultured two different open-ocean diatom species ( T. oceanica and Chaetoceros sp.) in a series of experiments at constant medium Zn concentration but at bioavailable medium Fe ranging from limiting to replete. We find that T. oceanica can maintain high growth rates and Zn uptake rates over the full range of bioavailable iron (Fe) investigated, and that the Zn taken up has a δ 66 Zn that is unfractionated relative to that of the bioavailable free Zn in the medium. The studied representative of the genus Chaetoceros, on the other hand, shows more significantly reduced Zn uptake rates at low Fe and records more variable biomass δ 66 Zn signatures, of up to 0.85‰ heavier than the medium. We interpret the preferential uptake of heavy isotopes at extremely low Zn uptake rates as potentially due to either of the following two mechanisms. First, the release of extracellular polymeric substances (EPS), at low Fe levels, may preferentially scavenge heavy Zn isotopes. Second, the Zn uptake rate may be slow enough to establish pseudo-equilibrium conditions at the transporter site, with heavy Zn isotopes forming more stable surface complexes. Thus we find that, in our experiments, Fe-limitation exerts a key control that not only limits diatom growth, but also affects the Zn uptake physiology of diatoms. Uptake of heavy isotopes occurs under Fe-limiting conditions that drive extremely low Zn uptake rates. On the other hand, more rapid Zn uptake rates result in biomass that is indistinguishable from the external bioavailable free Zn pool. These experimental results can, in principle, explain the range of Zn isotopic compositions found in the real surface ocean, given the geographically variable interplay between Fe-limitation, Zn uptake rates, and the degree of organic complexation of oceanic Zn.